2014
DOI: 10.1111/ene.12511
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and white matter abnormalities in older adults: a cross‐sectional neuroimaging study

Abstract: Background and purpose: Morphological brain changes related to hypovitaminosis D have been poorly studied. In particular, the age-related decrease in vitamin D concentrations may explain the onset of white matter abnormalities (WMA) in older adults. Our objectives were (i) to investigate whether there was an association between serum 25-hydroxyvitamin D (25OHD) concentration and the grade of WMA in older adults and (ii) to determine whether the location of WMA was associated with 25OHD concentration. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 44 publications
2
40
0
Order By: Relevance
“…Although the biological mechanisms associating dementia risk with low VitD levels are not fully understood, low VitD status has been associated with increased white matter hyperintensities 46,47 and enlarged ventricular volumes. 48 Serum 25-OHD is also associated with reduced β-amyloid 1-42 concentrations in cerebrospinal fluid, 47 a recognized risk factor for incident dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Although the biological mechanisms associating dementia risk with low VitD levels are not fully understood, low VitD status has been associated with increased white matter hyperintensities 46,47 and enlarged ventricular volumes. 48 Serum 25-OHD is also associated with reduced β-amyloid 1-42 concentrations in cerebrospinal fluid, 47 a recognized risk factor for incident dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding brain vascular changes, experiments in rats showed that vitamin D attenuates cortical ischemia after cerebral arterial ligation . In humans, a meta‐analysis reported that those with hypovitaminosis D have more strokes than other groups, and a similar association was recently highlighted with cerebral small vessel disease . Among older adults, hypovitaminosis D was associated with an increased volume of white matter damage (WMD), specifically periventricular WMD, but not deep WMD …”
Section: Vitamin D and Brain Structurementioning
confidence: 99%
“…Besides its well‐known consequences, such as interference with bone metabolism and increased predisposition to certain cancers, several studies have investigated a possible correlation between vitamin D deficiency and cerebrovascular disease. However, results have been inconsistent, with some studies showing a relationship between both conditions while others were showing no association . It is also possible the occurrence of a reverse causation phenomenon, by which persons with a stroke are more prone to develop vitamin D deficiency as they are less likely to be exposed to direct sunlight.…”
Section: Exposure Effect Models Constructed With Vitamin D Deficiencymentioning
confidence: 99%